Garbhagriha (left) and mandapa (right) of Jabreshwar temple - Ghosh, Ayan (2023)
Built of black stone, the Jabreshwar Mahadev Temple is squeezed on a flat plinth along the slope of Jabreshwar Gali. An urban legend explains the quirky name of the temple because it was apparently built on land acquired by force (jabardasti). The entrance to the temple opens to Jabreshwar Gali from the side, because of buildings surrounding it on three sides.